STUDI TENTANG STRUKTUR KOMUNITAS LAMUN DAN FAKTOR-FAKTOR FISIKA DAN KIMIA YANG MEMPENGARUHI PERTUMBUHAN LAMUN DI KABUPATEN BANGKA TENGAH - DWI ROSALINA (Akuatik: Jurnal Sumberdaya Perairan, 2012)
Ketawai Island located in Bangka Belitung Province and includes a small island in Central Bangka Regency. Attention to seagrass ecosystems in the waters Ketawai is still lacking, thus causing more and more activities that threaten the sustainability of seagrass ecosystems. Data seagrass ecological information needed in order to dig up information about the presence of seagrass in quantitatively on the ketawai island of Bangka Island Central. This research was conducted to know the structure of seagrass communities in the waters of the island of Bangka Regency Ketawai Central by measuring the influence of environmental factors that affect the physical and chemical water seagrass ecosystem at research sites. Method of determining the sampling point using a purposive sampling method and chemical physical parameters measured water temperature, salinity, pH, current, brightness, and depth. Species seagrass are found consisting of 6 (species), namely Enhalus acoroides and Thallassia hemprichii, Halodule uninervis, Cymodocea rotundata, Syringodium isoetifolium, and Halodule pinifolia. Seagrass diversity in the waters of the island Ketawai categorized with low until medium of 0.7160 to 2.0886, the value of seagrass categorized as very high uniformity with a range of 0.7160 to 0.9044, and the dominance of lowcategorized as high with a range of 0.2622 to 0 , 6835. The pattern of distribution of seagrass species Enhalus acoroides seagrass, Thalassia hemprichii, Halodule uninervis, and Cymodocea rotundata have value uniform distribution pattern and clustered distribution pattern is a type of seagrass Halodule pinifolia and Syringodium isoetifolium. Results of measurement of physical parameters and water chemistry at each station showed that seagrass species are able to grow in accordance with environmental conditions such as temperature, salinity, brightness, pH, depth, currents and the substrate is quite suitable for seagrass growth